Perlindungan Hukum Terhadap Pemegang Hak Milik Atas Tanah yang Dialihfungsikan Sebagai Jalan Raya - Anak Agung Dwi Jayantri; I Putu Gede Seputra; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
Land procurement is an activity of obtaining land which is indicated for development for the community in general which involves the land, which is offset by compensation from the government. The holder of land ownership rights must get legal protection, because the rights owned by the community must be protected so that the community gets legal certainty. So that the formulation of the problem used is 1) what is the legal protection of holders of land rights used for the public interest in making roads? 2) What are the Government's efforts towards the release of property rights to land used for the public interest in making roads? Normative legal research methods are used in this study. The results of the study showed that the inclusion of fair and just compensation for compensation was based on deliberation, and the community could file an objection to the form and or amount of compensation handed down by the government to the local District Court for holders of land rights in order to obtain legal protection. The form of government efforts in releasing ownership rights of a community land, namely money that is paid in compensation can be temporarily surrendered to the Court and for people who want to surrender their land without any objection, the community is entitled to tax incentives. Tax incentives are to minimize the cost of a tax so that tax costs become lighter.